SARC018_SPORE02: Phase II Study of Mocetinostat Administered with Gemcitabine for Patients with Metastatic Leiomyosarcoma with Progression or Relapse following Prior Treatment with Gemcitabine-Containing Therapy. (24th October 2018) - Choy, Edwin; Ballman, Karla; Chen, James; Dickson, Mark A.; Chugh, Rashmi; George, Suzanne; Okuno, Scott; Pollock, Raphael; Patel, Rajiv M.; Hoering, Antje; Patel, Shreyaskumar
Abstract : Histone deacetylase inhibitors (HDACi) can reverse chemoresistance, enhance chemotherapy-induced cytotoxicity, and reduce sarcoma proliferation in cell lines and animal models. We sought to determine the safety and toxicity of mocetinostat and its ability to reverse chemoresistance when administered with gemcitabine in patients with metastatic leiomyosarcoma resistant to prior gemcitabine-containing therapy. Participants with metastatic leiomyosarcoma received mocetinostat orally, 70 mg per day, three days per week, increasing to 90 mg after three weeks if well tolerated. Gemcitabine was administered at 1, 000 mg/m 2 intravenously at 10 mg/m 2 /minute on days five and 12 of every 21-day cycle. Disease response was evaluated with CT or MRI. Twenty participants with leiomyosarcoma were evaluated for toxicity. Median time to disease progression was 2.0 months (95% CI 1.54–3.12). Eighteen participants were evaluated for radiologic response by RECIST 1.1. Best responses included one PR and 12 SD. Tumor size reduced in 3 patients. Most common toxicities were fatigue, thrombocytopenia, anemia, nausea, and anorexia. One patient experienced a significant pericardial adverse event. No study-related deaths were observed. Rechallenging with gemcitabine by adding mocetinostat was feasible and demonstrated modest activity in patients with leiomyosarcoma. Further studies are needed to better define the role of HDAC inhibitors in patients with metastatic leiomyosarcoma.